DESAIN AWAL RUANG BAKAR PREMIXED UNTUK TURBIN GAS ULTRA MIKRO (TGUM) DENGAN MENGGUNAKAN PENDEKATAN TEMPERATUR ADIABATIK - Al Gifari, Muhamad Maris; Hartono, Firman; Darmanto, Prihadi Setyo; Reksowardojo, Iman Kartolaksono (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
The need to develop ultra-micro gas turbine (TGUM) applications is getting higher, especially as a portable energy source. Many applications whose energy requirements cannot be met by current batteries but can be handled by TGUM. The energy density of kerosene is 45 times greater than that of current batteries. The development of ultra-micro gas turbines has been carried out for more than 20 years. The challenge faced in the TGUM development process was manufacturing technology, but manufacturing developments continue to advance over time, meaning that one day high-speed bearing technology may be achieved. The development of an ultra-micro gas turbine can be started from the design of the combustion chamber. The basic concept of determining the initial size of the diameter as the initial reference length is widely available and established, but this reference is only for combustion chambers with non-premixed combustion. No one has discussed the determination of the size of the premixed combustion chamber. The basis for the initial determination of the combustion chamber in this article is the determination of the adiabatic temperature, and the energy balance equation which is simplified to become Black's Principle. This method describes the relationship between the diameter of the combustion chamber, airflow dilution portion and the flame propagation speed that must be met. This method also determines the value of the equivalence ratio, and also length of combustion chamber based on SHR (Space Heating Rate) that must be taken. The results of this method when entering the condition of the combustion chamber inlet 379 K, 2.05 bar, and outlet 879 K, 1.79 bar produce a reference decision of 5 cm diameter, flame speed of 6 m/s, equivalent ratio of 0.8 and 74% cooling portion for a gas turbine mass flow rate of 85.7 g/s.